What is the best treatment for adult distal 1/3 humerus fractures? Best treatment for humerus fractures - Yilmaz, Mehmet; Ulusoy, Ibrahim; Gurger, Murat; Atilgan, Numan (Bayrakol Medical Publisher, 2023)
Aim: Adult humeral fractures that do not extend to the elbow joint can be seen in low-energy trauma in the elderly and high-energy trauma in the young. Fractures of the distal 1/3 of the humerus are treated with surgical and non-surgical methods. Our study aimed to evaluate the functional and radiological results of the distal 1/3 humerus fractures, which do not involve the joint, by comparing the conservative and surgical treatments and the surgical techniques used. Material and Methods: Thirty-five patients with adult distal 1/3 humeral fractures that did not extend to the joint between January 2010 and October 2014 were included in the study. The cases were evaluated retrospectively. Results: Nine of the cases were female and 26 were male. The mean age of the patients was 33,6. The articular range of motion (ROM) of cases was measured at an average of 118,8 degrees, and extension loss was measured at an average of 7,14 degrees. The average Mayo score of cases was measured at 87. Mono plaque osteosynthesis was applied to 20 of all cases (Group I), double plate osteosynthesis was applied to 11 (Group II), and conservative treatment was applied to 4 (Group III). A statistically significant difference between Group I and Group II was not been determined regarding union time, complication, Mayo Score, Cassebaum's rating, ROM, and extension loss. According to surgical approaches applied to patients (lateral-posterior), while no statistical difference was determined regarding complications, union time, and ROM, a significant difference was determined regarding Mayo Score and extension loss. According to different determination methods, a statistical difference was not been determined regarding complications, ROM, extension loss, Mayo Score and union time. Discussion: We recommend surgery with a lateral approach to preserve the extensor mechanism in fractures of the distal 1/3 of the humerus.
Keywords: Humerus Distal Fractures; Surgical Treatment; Conservative Treatment; Mayo Score